Investigation of associations between the effects of COVID-19 fear on school administrators and nutrition and problematic eating behaviors - Karaköse, Turgut; Yirci, Ramazan; Basyigit, Hasan; Kucukcakir, Ali (Progress in Nutrition, 2021)
Summary. The current study aims to explore associations between fear of COVID-19 among school administrators and nutrition and problematic eating behaviors. The sample of the descriptive research patterned on the survey model consists of 266 school administrators who participated in the research voluntarily and were determined according to the disproportionate cluster sampling technique. The data of the study were collected with the “Fear of COVID-19 Scale” and the “Dutch Eating Behavior Questionnaire.” The results of the study revealed a positive relationship between school administrators’ COVID-19 fear and their nutritional behavior. This relationship was found to be higher in the “emotional eating” behavior dimension. Additionally, the COVID-19 fear levels of school administrators and their emotional eating behaviors differed according to the gender factor. In this context, female school administrators experienced higher COVID-19 fear levels and tended to be more prone to emotional eating behaviors. Again, the results of this study reveal that the fear of COVID-19 can significantly predict the nutritional behaviors of school administrators in the dimensions of external eating, emotional eating, and restrictive eating.